A dinâmica dos manguezais subtropicais no litoral norte de Santa Catarina durante o Holoceno tardio. - PINHEIRO, Vanessa da Conceição (Universidade Federal do Pará, 2019)
The goal of this work is identifying the establishment and expansion of mangroves on the northern coast of Santa Catarina during the Late Holocene. For this work, pollen data, 14C dating, organic geochemical (δ13C, C:N, TN and TOC) and results of sedimentary analyzes were integrated. These data were obtained from the analyses carried out from two sedimentary cores (SF7 and SF8) collected using a Russian sampler in the Babitonga Bay, northern coast of Santa Catarina. The data reveals a typical tidal channel and tidal plain deposits throughout the records. The tidal channel deposit was accumulated between > 1692 cal yr BP to ~ 667 cal yr BP, close to the bottom of the cores. This deposit is formed by fine-to-medium sand with parallel laminated sand (Sp facies), cross lamination (facies Sc), low angle planar lamination (Sb facies) and massive sand (Sm facies). The sedimentary deposit is characterized as a tidal plain around ~ 1223 cal yr BP, constituted by facies flaser heterolithic bedding (Hf), wavy heterolithic bedding (Hw), lenticular heterolithic bedding (H1) and parallel mud (Mp). The pollen content preserved along the tidal channel deposits reveals predominance of trees, shrubs, herbs and palms surroundings of the channel and on topographically higher regions. Only SF8 core was found mangroves pollen while the isotopic data revealed δ13C (-24.4 to -21.47 ‰), C/N ratio (4.77 to 20.81) with a strong contribution of marine organic matter and C3 terrestrial plants. The tidal channel was clogged and allowed the beginning of the deposition of the tidal plain. The deposit of the tidal plain has a large amount of plants fragments and pollen content characterized by predominance of herbs, trees, shrubs, palms and mangroves. The results of δ13C (-22.48 to -21.18 ‰) and C:N ratio (11.49 to 19.89) indicated the contribution of C3 terrestrial plants as well as contribution of marine organic matter. In addition, the mangroves beginning from approximately ~1692 cal yr BP with the genus Laguncularia and Avicennia, still at the edge of the tidal channel. Around ~586 cal yr BP was observed the mangrove development with a Rhizophora genus. The Laguncularia and Avicennia were initially established in sandy substrates and then also occupied in silty sandy soil. In the tidal plain environment, the genus Rhizophora was established in mud substrate. The mangroves of this region settled in the topographically higher regions and later expanded to the lower and closest regions of the Babitonga bay, possibly due to the decrease of the relative sea level recorded during the late Holocene as well as the migration and filling of the tidal channels. The occurrence of Rhizophora pollen close to the surface probably was a result of the temperature rise during the Late Holocene.